Genome sequence of the squalene-degrading bacterium Corynebacterium terpenotabidum type strain Y-11T (= DSM 44721T). Issue 3 (November 2014) - Rückert, Christian; Albersmeier, Andreas; Al-Dilaimi, Arwa; Bednarz, Hanna; Niehaus, Karsten; Szczepanowski, Rafael; Kalinowski, Jörn
Abstract Corynebacterium terpenotabidum Takeuchiet. al 1999 is a member of the genusCorynebacterium, which contains Gram-positive and non-spore forming bacteria with a high G+C content.C. terpenotabidum was isolated from soil based on its ability to degrade squalene and belongs to the aerobic and non-hemolyticCorynebacteria . It displays tolerance to salts (up to 8%) and is related toCorynebacterium variabile involved in cheese ripening. As this is a type strain ofCorynebacterium, this project describing the 2.75 Mbp long chromosome with its 2, 369 protein-coding and 72 RNA genes will aid theG enomic E ncyclopedia of B acteria and A rchaea project.